Coupling Model of Music Education and Fujian Ecoculture Based on Genetic Algorithm. (1st April 2022) - Zheng, Xiaofang
Abstract : Public music education in universities can promote the improvement of students' moral feelings, the cultivation of students' cultural quality, and the development of students' physical and mental health. Music education is an essential part of quality education in universities. The relationship between music education and Fujian ecological culture is investigated in this paper. The evaluation index system of regional music education and Fujian ecological culture construction is constructed from five aspects, green economy, social development, resource conservation, environmental pressure, and ecological culture, based on GA (genetic algorithm) and regional characteristics of music education and Fujian ecological culture construction. The principal component clustering coupling model is built on this foundation. According to the findings, Fujian's ecocultural construction is still in the process of coordinating and integrating economic, ecological, and cultural systems, and it is necessary to follow the path of regional integration, coordinate the development steps of each subsystem as a whole, and promote the region's coordinated development.